2010
DOI: 10.1111/j.1743-6109.2010.01780.x
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine Aspects of Male Sexual Dysfunctions

Abstract: Introduction Endocrine disorders may adversely affect men’s sexual function. Aim To provide recommendations based on best evidence for diagnosis and treatment of endocrine-related male sexual dysfunctions. Methods The Endocrine Aspects of Male Sexual Dysfunctions Committee, including 11 members from eight countries and four continents, collaborated with the E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
205
2
16

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2
2

Relationship

4
5

Authors

Journals

citations
Cited by 182 publications
(227 citation statements)
references
References 254 publications
4
205
2
16
Order By: Relevance
“…However, it could be hypothesized that intraprostatic level of DHT could be more important than the level of serum testosterone for the growth of the prostate (Isaacs et al 1983), thus explaining this lack of association between serum testosterone level and prostate overgrowth. In contrast, some uncontrolled studies have reported a gradual improvement in the International Prostate Symptom Score (IPSS) following long-term testosterone therapy in men with hypogonadism and/or metabolic syndrome (MetS) (see review in Buvat et al (2010)). A small randomized controlled trial with testosterone enanthate in 23 men with BPH tends to support these findings, with a significant decrease in the IPSS score, maximum flow rate, and voided volume in the testosterone group but not in the 23 untreated controls (Shigehara et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…However, it could be hypothesized that intraprostatic level of DHT could be more important than the level of serum testosterone for the growth of the prostate (Isaacs et al 1983), thus explaining this lack of association between serum testosterone level and prostate overgrowth. In contrast, some uncontrolled studies have reported a gradual improvement in the International Prostate Symptom Score (IPSS) following long-term testosterone therapy in men with hypogonadism and/or metabolic syndrome (MetS) (see review in Buvat et al (2010)). A small randomized controlled trial with testosterone enanthate in 23 men with BPH tends to support these findings, with a significant decrease in the IPSS score, maximum flow rate, and voided volume in the testosterone group but not in the 23 untreated controls (Shigehara et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Beyond 6 months, TRT should be continued only in cases of clinical benefit. 77 Caution is warranted in men with a history of congestive heart failure (risk of fluid retention); repletion goals should be in the middle range (ie, 350-600 ng/dL) for this group. In patients older than 70 years and those with chronic illness, the consensus panel suggests use of an easily titratable testosterone formulation (eg, gel, spray, or patch) rather than intermediate and long-acting injectable formulations.…”
Section: Treatment Additional Cardiovascular Evaluation and Referralmentioning
confidence: 99%
“…In addition, signs and symptoms of hypogonadism are quite similar, irrespective of the disease origin; in other words, the clinical phenotype can be identical for primary or secondary hypogonadism. [2][3][4] However, the clinical phenotype is very different according to the age of hypogonadism onset, which can be used as an alternative classification. Table 1 reports the new age-ofonset-based classification of male hypogonadism.…”
Section: Classification Of Male Hypogonadism: Towards a Revisionmentioning
confidence: 99%
“…5,19,20 Although they differ in their proposed T thresholds for the biochemical definition of hypogonadism, [2][3][4] all the Andrology Society guidelines recognize that the presence of hypogonadism-related symptoms is the cornerstone to defining a clinically relevant hypogonadism. It has been universally recognized that diagnosis of androgen deficiency should be made only in symptomatic men with unequivocally low serum T levels, as neither marker is consistently reliable alone.…”
Section: Classification Of Male Hypogonadism: Towards a Revisionmentioning
confidence: 99%